Islam at 250 Studies in Memory of G.H.A. Juynboll - Sijpesteijn, Petra; Adang, Camilla (Leiden Studies in Islam and Society, 2020)
This volume, which pays tribute to the work of G.H.A. Juynboll, is a collection of original articles on the state of Islamic sciences and Arabic culture in the early phases of their crystallization.; Readership: Specialists and advanced students interested in early and medieval Islam and the various branches of Islamic learning and literature, such as hadith scholarship, Qur'anic studies, history, book lore and grammar.